Characterization of novel semiconductor lasers - Neo, Ting Heng (2018)
Lasers have become an integral part of our life and technology with Quantum Cascade Laser (QCL), a developing technology with great potential for various applications. Within QCL, there are mid-infrared QCL and Terahertz, THz QCL, each with their own function and design considerations. The project covers the analysis and comparison of the QCL devices through literature review and characterization experiment. From research, QCL design considerations is known while differences between mid-infrared QCL and THz QCL is noted such as having different waveguides. This is followed by characterization of electrical and optical properties of the laser. A working sample was found to be operable under cryogenic cooling at 80K in the mid-infrared regime at about 10 µm with output power in the milliwatt range. Comparison with data from other researchers on THz shows similarities between the two devices in terms of output characterization. Primary difference between both device types lay mainly in operation wavelength and waveguide material used. The results combined with knowledge from the literature review serves to set a direction for improvement in QCL technology.